Рассмотрение споров Европейским судом по правам человека - Сосна, Александр (My University, 2006)
Necessity of international legal protection of human rights has led to formation of the European court under human rights. Analyzing activity of the European court under human rights it is possible to draw a conclusion that the given activity not always positively influences development of the legislation of the European countries.